Chapters of dependency grammar a historical survey from antiquity to Tesnière - Imrényi, András; Mazziotta, Nicolas (Studies in language companion series ;, 2020)
"Was Tesnière the founding father of dependency grammar or merely a culmination point in its long history? Leaving no doubt that the latter position is correct, Chapters of Dependency Grammar tells the story of how dependency-oriented grammatical description developed from Antiquity up to the early 20th century. From Priscian's Rome to Dmitrievsky's Russia, from the French Encyclopaedia to Stephen W. Clark's school grammars in 19th century America, it is shown how the concept of dependencies (asymmetric word-to-word relations) surfaced again and again, assuming a central place in syntax. A particularly intriguing aspect of the storyline is that even without any direct contact or influence, authors were making key breakthroughs in similar directions. In the works of Sámuel Brassai, a Transylvanian polymath, and Franz Kern, a German grammarian, the first dependency trees appear in 1873 and 1883, respectively, predating Tesnière's stemmas by several decades"--